Análisis comparativo del nivel de recaudación monetaria por pago de impuestos y servicios prediales en el Gobierno Autónomo Descentralizado del Cantón Vinces durante el periodo 2018 – 2019 - Viteri Carriel, Marwin Javier (2020)
The objective of this research is to analyze and compare the monetary collection of tax payments and property services. To carry out the comparative analysis, it was necessary to request the monetary income collected for the years 2018 - 2019 and then compare them to determine the level of monetary collection for tax payments and property services in the Decentralized Autonomous Government of the Canton Vinces, taking into account that when performing This analysis shows the problems that the Municipal GAD has for the collection of taxes and the factors for which taxpayers do not pay on time and are delayed when paying taxes, the same that generates a change in what is has had budgeted in the year. The results of the horizontal analysis provided information to reach the conclusion, where it should be adjusted and compared with the growth and performance goals set.